Performance evaluation of multi carrier modulation techniques for HF frequency selective fading channel - Senawi, Ahmad Sazali; Sha'ameri, Ahmad Zuri (IEEE, 2002)
Multipath fading in HF channels causes time-delay spread that limits the maximum symbol rate, and frequency selective fading that attenuates some frequency bands compared to others. Multi-carrier modulation techniques, Multi-carrier ASK (MCASK) and Multi-camer PSK (MCPSK), can be used to ensure reliability of transmission and high data transmission rate. The bit-error rate (BER) performance is compared between single frequency modulation such as Amplitude Shiil-Keying (ASK) or Phase Shiil-Keying (PSK) and them ulti-carrier modulation in the presence of additive white Gaussian noise and a combination of multipath fading and additive white Gaussian noise. On the average, the BER performance is better for the multi-carrier modulation compared to the single carrier modulation under multipath fading conditions.